Convergences between digital curation and information design in the post custodial context of information science - Jorente, Maria José Vicentini [UNESP]; Landim, Laís Alpi [UNESP]; Apocalypse, Simão Marcos [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2021)
Objective: Identify the approximations between Digital Curation (DC) and Information Design (ID) in the context of Information Science (IS) and point out the contributions of these convergences to the efficiency and effectiveness of information curation on Web environments. Methodology: The methodology applied theoretical and exploratory with a qualitative approach, from bibliographic searches and systematization of the retrieved data. Thus, the main concepts of DC and ID as disciplines in the context of IS were retrieved, the convergences between the disciplines in the context of IS as an interdisciplinary area were presented and discussed. Results: The curation of digital information according to the criteria of the DC provides subsidies to improve the processes of each stage of its life cycle. ID and its dimensions, in turn, subsidize the planning and development of digital environments with a focus on improving the efficiency and effectiveness of the information communicated. In the theoretical-practical scope, the convergences between the actions of DC and the dimensions of ID provide opportunities for their multidirectional complementation. Considerations: The convergences between DC and the ID were demonstrated by the combination of elements present in subgroups of DC actions with elements present in the systematization of the ID in dimensions. There were points in common between the two disciplines that indicate the need for the convergence of their resources in the search for solutions to problems involved in the curation of digital information. The hypothesis that the two disciplines converge and potentialize solutions of complex informational problems in this context is confirmed.
Convergências entre a curadoria digital e o design da informação no contexto pós custodial da ciência da informação
Keywords: Digital curation; Information and technology; Information design